2002
DOI: 10.2337/diabetes.51.5.1453
|View full text |Cite
|
Sign up to set email alerts
|

A Potent and Highly Selective VPAC2 Agonist Enhances Glucose-Induced Insulin Release and Glucose Disposal

Abstract: Pituitary adenylate cyclase-activating peptide (PACAP) and vasoactive intestinal peptide (VIP) activate two shared receptors, VPAC1 and VPAC2. Activation of VPAC1 has been implicated in elevating glucose output, whereas activation of VPAC2 may be involved in insulin secretion. A hypothesis that a VPAC2-selective agonist would enhance glucose disposal by stimulating insulin secretion without causing increased hepatic glucose production was tested using a novel selective agonist of VPAC2. This agonist, BAY 55-98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
115
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 55 publications
5
115
1
Order By: Relevance
“…Several studies have shown that PACAP and PACAP receptor agonists may have therapeutic potential in arthritis and diabetes, respectively [49,50]. Thus, a better understanding of the mechanisms by which PACAP is released and functions in the skin may assist in the creation of new therapies for Th1-mediated skin diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that PACAP and PACAP receptor agonists may have therapeutic potential in arthritis and diabetes, respectively [49,50]. Thus, a better understanding of the mechanisms by which PACAP is released and functions in the skin may assist in the creation of new therapies for Th1-mediated skin diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis was performed by hydrolysis in 6 N HCl, then applied through an amino acid analyzer, typically accurate within Ͻ2%. Competition Binding Assay and cAMP Scintillation Proximity Assay (SPA)-PACAP competition binding and cAMP accumulation assay were performed as described previously (5).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, clinical applications will require selective activation of a particular receptor to minimize potential side effects mediated by the other receptors. For example, we have previously demonstrated that VPAC2 activation induces glucose-dependent insulin secretion without the undesired side effects mediated by VPAC1 such as watery diarrhea (5). Therefore, to provide a potential therapy for type 2 diabetes, VPAC2 selectivity is an absolute requirement.…”
mentioning
confidence: 99%
“…However, VPAC2 stimulation produces particular actions such as vasodilation, tachycardia and water retention (Farnham et al, 2011;Tsutsumi et al, 2002;Warren et al, 1992), and those effects would limit its use as a neuroprotective drug. Therefore, a PACAP derivative with an improved metabolic stability and the capacity to activate the PAC1 (anti-apoptotic) receptor, or simultaneously the PAC1 and VPAC1 (anti-inflammatory) receptors, without stimulating VPAC2, would be of great interest.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Thus, modulation of TNF-α should be an neuroprotective effects linked to a decrease of neuronal apoptosis and a reduction of inflammation. However, besides its neuroprotective effects, it has also been reported that PACAP, through VPAC2 receptor activation, can generate adverse effects such as hypotension, water retention, and tachycardia (Deguil et al, 2010;Farnham et al, 2011;Inglott et al, 2012;Mirfendereski et al, 1997;Tsutsumi et al, 2002;Warren et al, 1992). Also, it has been shown that a VPAC2 agonist exerts deleterious effects in a stroke model (Darsalia et al, 2013).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%